Global Cerebral Infarction After In-hospital Cardiac Arrest (Ictus, 2023)
Clinical Image on "Global Cerebral Infarction After Hospital Cardiac Arrest" presented in volume 4 issue 1 of 2023 of Ictus.
Keywords: Ishcemic stroke; Brain death; Cardiac arrest